Tropical cyclones in Mozambique: evolutionary trend and relationship with climate variability and sea surface temperatures - Sadique, Estevão (2024)
Mozambique, located in the Southwest Indian Ocean (SWIO), is bordered by the Indian Ocean from North to South, creating a waterway known as the Mozambique Channel (MC), delimited by latitudes 10°-27° South and longitudes 30°-50° East. Due to its geographical position, both the MC and SWIO are frequently impacted by extreme events such as heatwaves, cold spells, droughts, floods, and tropical cyclones. This study aimed to analyze the pattern of tropical cyclones that have affected Mozambique between 1980 and 2022, investigating their evolutionary trends and their relationship with global climate change. Observational data provided by the Mozambique National Institute of Meteorology (INAM) and modeled data (Era5 Land, National Oceanic and Atmospheric Administration-NOAA, and Copernicus Climate Change Service-CCS) were used. The methods employed included the Mann-Kendall Test, Empirical Orthogonal Teleconnections, and calculation of Extreme Precipitation Events. The results indicated that tropical cyclones exhibit a cyclical pattern, occurring annually with some years experiencing no cyclones, though such cases are rare. It was also observed that the pattern of Sea Surface Temperature (SST) in the Indian Ocean basin, including the Mozambique Channel, has been changing, possibly explaining the recent increase in the number of cyclones in the MC. The SST baseline has recently stabilized in the MC, influencing precipitation patterns in the region. These findings are concerning for Mozambique, especially in light of current IPCC projections indicating a global average temperature increase of around 3°C by the end of the 21st century. Keywords: Mozambique. Tropical Cyclones. Climate Change. SWIO. MC.